2015
DOI: 10.1182/blood-2014-10-604561
|View full text |Cite
|
Sign up to set email alerts
|

R-MPV followed by high-dose chemotherapy with TBC and autologous stem-cell transplant for newly diagnosed primary CNS lymphoma

Abstract: • We conducted a phase-2 study in newly diagnosed PCNSL utilizing R-MPV and HDC with ASCT.• Excellent disease control and OS (2-year PFS: 79%) were observed, with an acceptable toxicity profile and minimal neurotoxicity.High-dose methotrexate-based chemotherapy is the mainstay of treatment of primary central nervous system lymphoma (PCNSL), but relapses remain frequent. High-dose chemotherapy (HDC) with autologous stem-cell transplant (ASCT) may provide an alternative to address chemoresistance and overcome th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
276
5
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(304 citation statements)
references
References 44 publications
18
276
5
5
Order By: Relevance
“…29 Antonio Omuro et al previously conducted a single center phase 2 study in newly diagnosed PCNSL utilizing the R-MPV induction therapy and HD-AC, followed by consolidation HDC-ASCT with thiotepa, busulfan, and cyclophosphamide (TBC). 30 In their series, excellent disease-free control and OS (3-year OS, 81%; PFS, 79%) were observed, with an acceptable toxicity profile and minimal neurotoxicity. 30 Interestingly, a small phase 2 study suggested that HDC-ASCT could replace consolidation radiotherapy, with a 3-year OS of 77%.…”
Section: Discussionmentioning
confidence: 99%
“…29 Antonio Omuro et al previously conducted a single center phase 2 study in newly diagnosed PCNSL utilizing the R-MPV induction therapy and HD-AC, followed by consolidation HDC-ASCT with thiotepa, busulfan, and cyclophosphamide (TBC). 30 In their series, excellent disease-free control and OS (3-year OS, 81%; PFS, 79%) were observed, with an acceptable toxicity profile and minimal neurotoxicity. 30 Interestingly, a small phase 2 study suggested that HDC-ASCT could replace consolidation radiotherapy, with a 3-year OS of 77%.…”
Section: Discussionmentioning
confidence: 99%
“…Ha kellő tapasztalat és gyakorlat rendelkezésre áll, akkor lehet R-CHOP14-protokollt is alkalmazni, amelyből 6 ciklus is elegendő, de javasolt a +2 ciklus rituximab alkalmazása. Amennyiben a kiindulási betegség bulky jellegű volt, akkor javasolt a kemoterápia végén a kiindulási bulky terület involved field (IF) irradiációja csökkentett dózissal (30)(31)(32)(33)(34)(35)(36). Az agresszív, nagy rizikójú csoportba tartozó (IPI) betegek esetén az első vonalbeli kemoterápia után indokolt lehet az autológ csontvelő-transzplantáció elvégzése is, mivel egy viszonylag új tanulmány alapján a 2 éves OS transzplantá-cióval 82%, míg transzplantáció nélkül csak 64% [30].…”
Section: A Dlbcl Kezelése Maunclassified
“…Az R-MPV (rituximab, metorexát, procarbazin, vincristin) 2 hetente alkalmazva, majd fiatalabb betegeken a Thiotepa-Busulfan-Cytoxan kondicionálással autológ őssejttranszplantáció nagyon biztató eredményeket mutat, mivel 2 évnél az OS 80% és platót képez [33]. A rituximab nagy dózisú (3,5 g/m 2 ) metotrexát adásával még egészen idős, akár 90 éves betegekben is biztonsággal alkalmazható.…”
Section: A Dlbcl Kezelése Maunclassified
“…Morphologically, ~95% of these tumors are diffuse large B cell lymphoma (DLBCL), according to the new World Health Organization classification (5). Although the prognosis of PCNSL has been improved by optimal systemic treatment based on high-dose methotrexate (HD-MTX) (6)(7)(8), the overall survival (OS) of the majority of patients remains poor. This underlines the need to identify prognostic biomarkers for potential therapeutic targets and risk-stratified treatment.…”
Section: Introductionmentioning
confidence: 99%